Polymer brush lubrication of the silicon nitride–steel contact: a colloidal force microscopy study. Issue 68 (4th September 2017) - Watson, Simon; Dennington, Simon; Wang, Ling; Nie, Mengyan; Hinder, Steve; Stokes, Keith
Abstract : Surface initiated PMMA brushes are a promising candidate to lubricate the silicon nitride–steel contact under oil lubricated conditions. Abstract : A greener lubrication solution for the steel–silicon nitride hybrid contact is proposed. The utilisation of surface-initiated (SI) activators-regenerated-by-electron-transfer (ARGET) atom-transfer radical polymerisation (ATRP) is employed to produce an oleophilic polymer brush which is based on methyl methacrylate. The current study presents the synthesis and characterisation of poly methyl methacrylate brushes. X-ray photoelectron spectroscopy, contact angle, gel permeation chromatography and atomic force microscopy were used to characterise the initiators and brushes. The lubricating effects of the polymer brushes under dry and swollen states were elucidated by lateral force microscopy with a steel colloid with a normal load in the nanoscale range. By testing in water and in poly α-olefin (PAO) this work shows that the frictional response of surface initiated polymers is highly dependent on the interaction between polymer brushes and fluid.